In Aid We Trust : Hearts and Minds and the Pakistan Earthquake of 2005 - Andrabi, Tahir (2012)
Winning "hearts and minds" in the Muslim world is an explicitly acknowledged aim of U.S. foreign policy and increasingly, bilateral foreign aid is recognized as a vehicle towards this end. The authors examine the effect of aid from foreign organizations and on-the-ground presence of foreigners following the 2005 earthquake in Northern Pakistan on local attitudes. They show that four years after the earthquake, humanitarian assistance by foreigners and foreign organizations has left a lasting imprint on population attitudes. Measured in three different ways those living closer to the fault-line report more positive attitudes towards foreigners, including Europeans and Americans; trust in foreigners decreases 6 percentage points for every 10 Kilometers distance from the fault-line. In contrast, there is no association between distance to the fault-line and trust in local populations. Pre-existing differences in socioeconomic characteristics or population attitudes do not account for this finding. Instead, the relationship between trust in foreigners and proximity to the fault-line mirrors the greater provision of foreign aid and foreign presence in these villages. In villages closest to the fault-line, foreign organizations were the second largest providers of aid after the Pakistan army (despite reports to the contrary aid provision by militant organizations was extremely limited, with less than 1 percent of all respondents reporting any help from such organizations). The results provide a compelling case that trust in foreigners is malleable, responds to humanitarian actions by foreigners and is not a deep-rooted function of local preferences.